1996
DOI: 10.1021/tx950076m
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Thyroid Peroxidase by Dietary Flavonoids

Abstract: Flavonoids are widely distributed in plant-derived foods and possess a variety of biological activities including antithyroid effects in experimental animals and humans. A structure-activity study of 13 commonly consumed flavonoids was conducted to evaluate inhibition of thyroid peroxidase (TPO), the enzyme that catalyzes thyroid hormone biosynthesis. Most flavonoids tested were potent inhibitors of TPO, with IC50 values ranging from 0.6 to 41 microM. Inhibition by the more potent compounds, fisetin, kaempfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(134 citation statements)
references
References 18 publications
10
119
1
4
Order By: Relevance
“…The first step is iodination of thyroglobulin tyrosyl residues, followed by oxidative coupling to yield T 4 and T 3 . Inhibition of porcine TPO activity is a mechanism common to many classes of synthetic antithyroid compounds (27)(28)(29)(30)(31) and naturally occurring flavonoids (32,33). Lactoperoxidase (LPO) is often used as a model for TPO, based on many shared structural and functional properties.…”
Section: Biosynthesis Of Thyroid Hormones and Inhibition By Antithyromentioning
confidence: 99%
“…The first step is iodination of thyroglobulin tyrosyl residues, followed by oxidative coupling to yield T 4 and T 3 . Inhibition of porcine TPO activity is a mechanism common to many classes of synthetic antithyroid compounds (27)(28)(29)(30)(31) and naturally occurring flavonoids (32,33). Lactoperoxidase (LPO) is often used as a model for TPO, based on many shared structural and functional properties.…”
Section: Biosynthesis Of Thyroid Hormones and Inhibition By Antithyromentioning
confidence: 99%
“…In a related study, Corvazier and Maclouf (17) demonstrated that naringenin (500 M) is an irreversible inhibitor of both LOX and COX pathways. Furthermore, naringenin has been shown to inhibit myeloperoxidase (MPO) (approximate IC 50 ‫ס‬ 150 M) (22). MPO secreted by macrophages and activated neutrophils is a potent catalyst of LDL oxidation in vitro and colocalizes with macrophages in human atherosclerotic lesions (40).…”
Section: Antioxidant Antithrombotic Antiinflammatory and Vasodilatmentioning
confidence: 99%
“…Its active components are reported to have several biological properties, including cancer chemoprevention, inhibition of tumour cell growth, antiviral and antiinflammatory activities [1], antioxidant activity [2,3] and inhibitory effects on several enzymes, such as aromatase [4,5], angiotensin converting enzyme [6] and thyroid peroxidase [7]. Dried leaves of C. sinensis contain polyphenols (30%-36%), principally flavanols, more commonly known as catechins [8].…”
Section: Introductionmentioning
confidence: 99%